Blended teaching readiness of EFL instructors and their perceptions about blended learning in English preparatory schools: a case from Turkey - Gultekin, Kursat; Mede, Enisa (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2024)
This study aimed to investigate the blended teaching readiness of the EFL instructors (N = 102) employed in an English preparatory school of a state university in Istanbul, Turkey. The study also aimed to explore the perceptions of the instructors about blended teaching practices. The quantitative data was collected from the Blended Teaching Readiness Scale (Archibald et al., 2021). The statistical analysis of the quantitative data (IBM SPSS 28) reported that the instructors were ready for blended teaching. Specifically, there was no significant difference between the blended teaching readiness and their education level apart from their teaching experience. Additionally, a significant correlation existed between the blended teaching readiness of the instructors and their ability to use the computer for teaching needs. Meanwhile, the qualitative data gathered through semi-structured interviews with the instructors (N = 10) emphasized the importance of the theme, interaction, integration of face-to-face and online environments, needs and required skills, and teachers' beliefs for blended teaching readiness. The results of the study provide implications and suggestions for blended teaching in an EFL context.
Keywords: Blended learning; blended teaching readiness; blended teaching competencies; EFL; Education & Educational Research